抜歯後出血を契機に診断された先天性第Ⅴ因子欠乏症の1例 - 薮田, 達雄; 葛城, 勝彦; 妙中, 泰之; 藤田, 茂之; 和田, 健; 森田, 展雄 (日本口腔外科学会雑誌, 2011)
Blood coagulation factor V is a common factor involved in both intrinsic and extrinsic pathways of coagulation; its congenital deficiency is rare. We report a case of congenital factor V deficiency detected because of bleeding after tooth extraction. A 60-year-old man visited our department because of continued bleeding after tooth extraction. We were able to stop the bleeding by local hemostatic measures. However, prothrombin time （PT） was found to be prolonged on a screening blood test. After further evaluation at the Department of Hematology/Oncology, prolongations of both PT and activated partial thromboplastin time （APTT） were confirmed, and the factor V activity was 4.7 ％, which is very low. After correction of the PT and APTT values by a cross-mixing test, the possibility of an acquired coagulation factor inhibitor was ruled out. The patient was then given a diagnosis of congenital factor V deficiency. He visited our department again to undergo extraction of the right upper first premolar. After consultation with the Department of Hematology/Oncology, tooth extraction was performed under local anesthesia concurrently with transfusion of fresh frozen plasma. Factor V activity was corrected to 22.3 ％ from 3.8 ％, and the PT and APTT values improved. Postoperative bleeding was controlled by local hemostatic measures using oxidized cellulose and a gingival pack.